2006
DOI: 10.1111/j.1365-2850.2006.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health education for people with mental health problems: what can we learn from the literature?

Abstract: Research into sexual risk behaviour among people with 'severe' mental health problems suggested that they are likely to engage in high-risk sexual behaviour, for a number of reasons, putting them at risk of sexually transmitted diseases. The aim of this review is to describe approaches, content and outcomes of sexual health education programmes, developed and implemented for people with mental health problems. A literature review from 1980 to 2005 was carried out using the electronic databases CINAHL, PsycINFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 30 publications
2
88
0
3
Order By: Relevance
“…Des services en santé mentale ont dispensé des programmes d'éducation sexuelle aux usagers. Higgins et al (2006) ont recensé quatorze études portant sur l'éducation à la santé sexuelle des personnes souffrant d'une maladie mentale. Ils ont pu constater que les programmes ont été béné-fiques puisque les études rapportent une diminution des comportements sexuels à risque chez les participants.…”
Section: Des Pratiques De Reconnaissance Des Droits Sexuels De L'usagunclassified
“…Des services en santé mentale ont dispensé des programmes d'éducation sexuelle aux usagers. Higgins et al (2006) ont recensé quatorze études portant sur l'éducation à la santé sexuelle des personnes souffrant d'une maladie mentale. Ils ont pu constater que les programmes ont été béné-fiques puisque les études rapportent une diminution des comportements sexuels à risque chez les participants.…”
Section: Des Pratiques De Reconnaissance Des Droits Sexuels De L'usagunclassified
“…with human immunodeficiency virus (HIV). 2,19,20 HIV infection rates among people with SMI have been estimated to be approximately 6.9%, much higher than rates for the general US population for the same time period, estimated to be 0.4%. 18 The HIV infection range among those with SMI is reported to be 3-23%, with the highest rates found among those with SMI and substance abuse disorders.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…36,37 Mental health nurses and other professionals working with people with SMI would be well placed to include sexual health as part of their contribution to health promotion. 20 A study by Apantaku-Olajide et al 38 used a survey questionnaire to determine mental health patients' attitude to psychotropic medication for sexual dysfunction and found that participants were willing to discuss their sexual problems with health-care professionals. However, staff may require specific training in order to deliver such interventions.…”
Section: Current Service Provisionmentioning
confidence: 99%
See 2 more Smart Citations